Russian literary history for advanced readers, with plenty of textual illustrations: Lukyanova, I.: Once upon a time there was Russian literature: From Ancient Rus' to the XX century. Publishing House AST.2023. Moscow. Pp. 348. ISBN 978-5-17-154945-9 - Váradi, Ferenc (Slavica, 2024)
Lukyanova's book was published in 2023. The author is a journalist who studies Russian literature and its history, and reviews it in a rather unique way. The purpose of the review is to determine what genre Lukyanova's book can be classified as, and to find out what its uniqueness is manifested in.